The successful of online learning on student responsibility character during the COVID-19 pandemic - Aziz, Rahmat -; Nur, Muhammad Amin; Dilapanga, Raihan Retriansyah; Manasikan, Mega Arina; Muarofah, Ulfiatul - (Jurnal Pendidikan dan Pengajaran, 2022)
Learning activities to develop the character of responsibility during the COVID-19 pandemic have created difficulties for teachers as teaching guides and students as learning implementers. Teachers and students’ problems appropriately and wisely help shape satisfying forms of responsibility character in education. This paper aims to describe student responsibility behaviour in learning and analyze the roles of teachers during the learning process. This paper-based is on data collected from open questionnaires to 58 senior high schools in Manado North Sulawesi, Pasirian East Java, and Malang East Java. Data collection through interviews with seven teachers and two school principals. The data were analyzed using theme analysis techniques and reflective thinking. The results showed that responsive and proportionate teachers in delivering learning have succeeded in developing responsible behaviours towards students. Selection of the suitable learning model and positive school support has become a determinant of success for the learning process of student responsibility. This paper suggests the need for a more in-depth data collection method to understand cases comprehensively.